Purposeful Awareness and Its Role in Dealing with Extravagance and Religious Extremism - dehiri , samir (Journal of Social Sciences and Humanities, 2021)
The present study aims to provide an approach to deal with the phenomenon of extravagance and religious extremism. It attempts to diagnose some of the causes of extremism and intellectual deviation. The study also emphasizes the importance given to moderation by Islamic law, since this phenomenon is widely spread in Muslim societies nowadays, which has led to serious effects on Muslim countries. Using a descriptive and analytical approach, the findings show that the phenomenon of extravagance and religious extremism has a strong relationship with the purposeful awareness among members of society. Moreover, the purposes of Sharia play an important role in the treatment and dismantling of the discourse of extravagance and religious extremism. Therefore, the average Muslim has to be aware of the aims and secrets of Sharia so that all his actions can be moderated. Furthermore, the study proves the ability of Islamic thought to find a remedy to the crises and manifestations of religious extremism and extravagance.